A new method for assessing tibial torsion using computerized tomography in a pediatric population - Gavira, Nathaly; Cochard, Blaise; Guanziroli, Nastassia; Di Laura Frattura, Giorgio; Dayer, Romain; Ceroni, Dimitri (Frontiers in Pediatrics, 2024)
Purpose: Tibial torsion disorders may lead to abnormal gait, frequently leading to a consultation with a pediatric orthopedic surgeon. The present study evaluated an alternative method for assessing tibial torsion on computerized tomography (CT) images that considers the tibial distal axis to be equivalent to the geometric axis of the tibiotalar joint. Methods: One hundred CT scans were reviewed retrospectively, and four measurements were taken: proximal transtibial angle (PTTA), posterior margin tibial plateau angle (PMTPA), intermalleolar angle (IMA), and talar angle (TA). The tibial torsion angle was then calculated using these different angles. Results: The patient cohort comprised 38 girls and 62 boys, with a mean age of 12 ± 4.4 years. Median PTTA and PMTPA were -8.4° ± 14.7° and -8.8° ± 14.2°, respectively, with no statistically significant difference. Mean IMA and TA were 23° ± 16.2° and 17.2° ± 16.9°, respectively, with a statistically significant difference. Mean total measurement time per patient was 6'44'', with means of 2'24'' for PTTA, 36'' for PMTPA, 2'14'' for IMA, and 1'12'' for TA. Conclusion: Tibial torsion values may differ significantly depending on the axis chosen to define tibial orientation. At the level of the proximal tibia, the choice of PTTA or PMTPA had little influence on the calculation of the tibial torsion angle. There was a significant difference of 5.8° when measuring the distal tibia. Measuring the PMTPA and TA is probably more suited for use in clinical practice because their tracing is simple and faster.